Breast self-examination: Perceptions of 9th cycle nursing students at a private university in Chiclayo, 2023 - Viera Molocho, Shirley Nicol (2025)
Breast self-examination is a useful procedure to prevent breast cancer, despite its importance, there is little knowledge and inadequate practices in its performance, especially in the young population. The research was qualitative, with a descriptive design, whose objective was to describe and analyze the perception of breast self-examination in students of the IX cycle of nursing at a private university in Chiclayo, 2023. The population consisted of 44 students of the IX cycle of Nursing at the Santo Toribio de Mogrovejo Catholic University. The sampling was by non-probabilistic convenience; the sample was 13 students, obtained by saturation and redundancy, the data was collected through a semi-structured interview guide that has been validated by expert judgment and by pilot testing, the information obtained was analyzed through content analysis revealing the results in 4 categories: Breast self-examination: A method to prevent cancer, Recognizing the importance of breast self-examination, Describing the procedure of breast self-examination and Difficulties in breast self-examination: Time, ignorance, fears. Finally, the ethical and scientific rigor criteria were met throughout the development of the study. Concluding that nursing students recognize the value of breast self-examination to prevent cancer, face barriers such as lack of time, ignorance and fears, being necessary to implement strategies that overcome these difficulties and promote its practice.